Finding common ground : enhancing interaction between domestic and international students : guide for academics. - Arkoudis, Sophie; Yu, Xin; Baik, Chi; Chang, Shanton; Lang, Ian; Watty, Kim; Borland, Helen; Pearce, Amande; Lang, Josephine (Australian Learning and Teaching Council, 2010)
Guide for academics in how to harness the potential of student diversity and in particular how university teaching can promote interaction between students from diverse cultural and linguistic backgrounds. The guide was produced through a 2008-10 project exploring the benefits of, and obstacles to, interaction among students from diverse cultural and linguistic backgrounds. It sought to identify examples of practice that were successfully enhancing such interactions within Australian university teaching and learning environments. Findings from the study highlight the potential benefit of peer interaction for learning across diverse cultural and linguistic groups. From both the students' and staffs' perspectives, interaction among students form diverse backgrounds potentially leads to: increased awareness and understanding of different perspectives; better preparation for the workplace; improved English language skills of international students; and a greater feeling of belonging. [p.6, ed]